THE ROLE OF DATA-DRIVEN DECISION MAKING IN DIGITAL MARKETING STRATEGY: A LITERATURE REVIEW - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2026)
This study examines the role of Data Driven Decision Making (DDDM) in digital marketing strategies by exploring its benefits, challenges, and impact on the success of marketing campaigns. DDDM offers a more objective approach by leveraging data analytics to make more precise and relevant marketing decisions. With the ability to personalise customer experiences and identify real-time market trends, DDDM enables companies to increase consumer engagement and ROI efficiency. However, the adoption of DDDM also presents challenges, including the need for data analysis expertise, technology investment, and privacy and ethical issues in data collection. Through a literature review, this study confirms that companies that can overcome these challenges can achieve significant competitive advantages by making smarter and more effective information-based decisions in their digital marketing strategies.